Contributions a l’etude des nematodes libres du littoral roumain de la Mer Noire - Onciu, Teodora (Cercetări Marine - Recherches Marines, 2026)
This paper presents the systematic study of 14 species of free-living Nematoda in the infralittoral and supralittoral levels of the Romanian Black Sea coast. Nine of the mentioned species are new for the fauna of Romania. The description of De Man’s organ is completed for Metaparoncholaimus campylocercus. Some data are given about the post-embryonic development of the larval stages of Enoplus quadridentatus and Cyatholaimus gracilis.